2020
DOI: 10.1920/wp.ifs.2020.2920
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying domestic violence in times of crisis

Abstract: Recent contributions using police recorded calls-for-service and/or crime data to estimate impacts of COVID-19 lockdowns on the incidence of domestic violence (DV) have reported relatively modest effects. This may reflect a low reporting-propensity, exacerbated by the lockdown measures. Combining five years of daily Google Trends data for a set of DV-related search terms with daily data on DV crimes recorded by the London Metropolitan Police Service (MPS), we propose a method for generating a search-based DV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…We are aware, however, that our study methods and sampling may have precluded families with histories or experiences of abuse from participating. Their experiences would be very different, and indeed as mentioned previously, it appears that domestic abuse increased during lockdown in the UK (Anderberg 2020).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We are aware, however, that our study methods and sampling may have precluded families with histories or experiences of abuse from participating. Their experiences would be very different, and indeed as mentioned previously, it appears that domestic abuse increased during lockdown in the UK (Anderberg 2020).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, as pointed out by numerous domestic abuse charities, home is not experienced as a safe space for all. Indeed, during the first lockdown research using Google Trends showed a large increase in domestic-abuse-related internet searches during the first months of the pandemic (Anderberg 2020). In response to calls from activists and family organizations, in late April 2020 the government announced that isolation instructions did not apply to those who were experiencing domestic abuse (UK Home Office 2020).…”
Section: Uk Country Contextmentioning
confidence: 99%